포도 유전체 연구현황 및 전망 - 허윤영(Youn Young Hur); 정성민(Sung Min Jung); 윤해근(Hae Keun Yun) (Journal of plant biotechnology, 2015)
Grape is one of the important fruit crops around the world, and exposed to disease and pests, and internal or environmental stresses in the vineyards. Breeding and cultivation of new varieties of high quality-grapes resistant to diseases and pests and tolerant to stresses are the most important steps in the grape production. However, conventional breeding has laborious and time-consuming procedures in maintaining and selecting seedlings in the fields. Development of molecular breeding technology through understanding of molecular mechanism of useful traits can be used as an alternative strategy to improve the efficiency of grape breeding program by cross hybridization in grape development programs. The completion of the grape genome sequencing project provided the way to discover the novel genes and to analyze their functions. Comparative genomics, transcriptomic analysis, and the genome-wide identification and analysis of useful genes as well as development of molecular marker for valuable traits could provide novel insights into fruit quality and the responses to diseases and stresses, and can be used as important information in molecular breeding programs for grape development. 포도는 전 세계적으로 가장 많이 재배되는 과수 작물 중의 하나로서 재배과정에서 많은 병해충이나 기상재해와 같은 스트레스에 직면한다. 과실의 고품질과 더불어 병충해 저항성인 품종 또는 내재해성 품종을 육성하는 것은 포도 생산에서 매우 중요한 과정이다. 고전적인 교배 육종을 이용한 신품종의 개발은 포장을 관리하는 데에 많은 노동력과 비용이 요구되며 오랜 시간이 소요되는 단점이 있다. 유용형질을 지닌 새로운 품종의 개발에 이용할 분자육종기술은 포도 육종프로램에서 전통적인 교배육종효율을 증진시킬 수 있는 매우 유용한 기술로 여겨진다. 포도의 유전체 해독을 완성함으로써 신품종육성에 활용될 유용유전자를 대량으로 발굴할 수 있고, 기능을 분석하는데 큰 도움을 주고 있다. 포도의 비교유전체, 전사체, 후성유전체, 유전체에 근거한 유전자 발굴, 분자마커 개발 등의 연구는 과실의 품질, 병해와 스트레스에 대한 저항성 기작을 구명하는데 중요한 단서를 제공하고 포도 육종에 유용하게 활용될 것이다.